The development of Islamic thought in post-independent India an appraisal of the views of Abul Hasan Ali Nadwi on multireligious harmony and Muslim identity = Perkembangan pemikiran Islam era pasca kemerdekaan India: penilaian pandangan Abul Hasan Ali Nadwi tentang keharmonian kepelbagaian agama dan identiti Muslim - Ahmad Siddique, Khalil; Ali, Muhammad Mumtaz (International Islamic University Malaysia, 2019)
Post-Independent India is considered as an ethnically diverse multi-ethnic and multi-religious republic. Muslims as a minority are granted constitutional rights. However, the environment of the country was communalized against Muslims. Numerous Hindu-organizations disagree with Muslim minority rights especially their existence with different identity. They want to change the secular constitution of India and turn it to a Hindu state. Nevertheless, to eradicate and to put an end to this demand the contemporary Muslim scholars want to create an environment of mutual-relationship as an inevitable remedy for a peaceful co-existing between Muslims and Hindus. For this purpose, Muslims are asked to develop a healthy relationship with the people of other faiths; and they must contribute towards the development of the state; and they should convey the true message of Islam to them. This paper aims at shedding light on the role of Abul Hasan Ali Nadwi who recognized the pulse of the time and worked continuously through his writings and organizational activities for religious harmony. In this paper, our study covers Nadwi’s works and activities. Nadwi’s views for interreligious dialogues, communal harmony and Muslim identity will be explored and analysed. This study follows qualitative approach and depends on books, articles, online academic materials. The finding shows that Abul Hasan Ali Nadwi has enormously contributed to the development of Islamic thought in post-independent India.